Entangling capacity of global phases and implications for the Deutsch-Jozsa algorithm - Azuma, H; Bose, S; Vedral, V (2001)
The generation of entanglement through global phase functions was studied. Necessary and sufficient conditions for the application of global phases to the pure product state to result in entanglement were obtained. The maximum entanglement creation by global phases was considered as well as its corresponding examples.